The alternative life of RNA—sequencing meets single molecule approaches. Issue 11 (19th April 2017) - Fernández‐Moya, Sandra M.; Ehses, Janina; Kiebler, Michael A.
Abstract : The central dogma of RNA processing has started to totter. Single genes produce a variety of mRNA isoforms by mRNA modification, alternative polyadenylation (APA), and splicing. Different isoforms, even those that code for the identical protein, may differ in function or spatiotemporal expression. One option of how this can be achieved is by the selective recruitment of trans ‐acting factors to the 3′‐untranslated region of a given isoform. Recent innovations in high‐throughput RNA‐sequencing methods allow deep insight into global RNA regulation, whereas novel imaging‐based technologies enable researchers to explore single RNA molecules during different stages of development, in different tissues and different compartments of the cell. Resolving the dynamic function of ribonucleoprotein particles in splicing, APA, or RNA modification will enable us to understand their contribution to pathological conditions. Abstract :